Influence of cationic surfactants on the growth of gypsum crystals - Li Gang; Xiao Haiping; Liang Luntao; He Xiangyu; Qi Nana (Open Physics, 2023)
The effect of cationic surfactants on the growth of gypsum was evaluated under conditions of a simulated production process of gypsum desulfurization. We used a laser particle size analyzer and a microscope to determine the particle size and morphology. The growth rate of gypsum was determined by the equation for the rate of chemical reaction of CaSO4·2H2O. The results showed that the growth rate at a supersaturation ratio of 2.4 increased by 50% with 30 mg/L of a dodecyldimethylbenzylammonium chloride. The gypsum morphology changed from needle-like in the absence of additives to tabular in the presence of cationic surfactants, indicating that relatively thicker and larger crystals were formed. Finally, the investigated cationic surfactants were beneficial to the normal operation of the desulfurization process.